Analysis of wind farm expansion on example Poland - Dolega, W. (Видавництво Національного університету “Львівська політехніка”, 2004)
This paper describes a some elements of research project “Wind Farm” which was realised in Wroclaw University of Technology. In this paper, analysis of different conditions of wind power expansion in Poland is shown. This analysis is made on basis computational examples of 6 MW wind farm in Poland from the point of view of different groups of parameters. Four groups of conditions: wind, geographical, technical and economical are taken into consideration.
Keywords: 621